NUMERICAL ANALYSIS OF REINFORCED CONCRETE BEAM IN TWO-DIMENSIONAL FORM (Advances in Civil and Architectural Engineering, 2021)
This paper presents a numerical analysis of a reinforced concrete beam in which the concrete and reinforcement are above the yield strength of the material. Further, the procedure for determining the relationship between the cross-sectional forces and the deformations of the layered cross-section of a rod is described. For a short rod with reduced stiffness of the EI and EA cross-sections, a stiffness matrix with variable members is formed. The applicability of the proposed analysis method for the material nonlinearity in a beam calculation is demonstrated through a numerical example. The aim of the present paper is to show the flow of plastification and the load-deformation of the system nodes. Finally, the results of the manual deformation calculation system are compared with the results from SCIA software.